Oxytocin and Health 2021
DOI: 10.5772/intechopen.96527
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and Neuroprotective Effects

Abstract: The neurohormone oxytocin (OT), consisting of nine amino acids, is produced in the hypothalamus and secreted from the posterior lobe of the pituitary gland. Recent studies show that OT can affect the course of the disease and is promising in the treatment of neurodegenerative disorders, due to its therapeutic properties and benefits. Histological and biochemical findings of the studies on vincristine-induced neuropathy, cisplatin-induced cytotoxicity, diabetic neuropathy, rotenone-induced Parkinson’s disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…The potential clinical usefulness of OT as adjunctive drug therapy in PD patients would be therefore based also on the possibility to reduce the dopaminergic therapy side effects, including the impulsivity disorders mainly in patients with addictive behaviors. As a matter of fact, evidence in animal PD models is provided that OT administration may possess neuroprotective effects on dopaminergic neurons related to anti-inflammatory, antioxidant, and anti-apoptotic activities [103], that dopamine levels increased when OT was administrated [104], that the OT levels were decreased in the models, that OT supplementation rescued locomotor disabilities and anxiety-like behaviors [101], and that after intranasal administration OT concentrates in brain regions including the striatum [105]; nevertheless, studies investigating OT in PD clinical settings are still needed [106]. In fact, critical examinations appear fundamental for enabling the utilization of OT mechanisms as a curative tool in psychiatric disorders, in particular when considering that the understanding of how OT impacts social behavior is still insufficient, life experience can change the OT systems function, and the OT effects appear highly context-dependent [107].…”
Section: Potential Relevance Of Striatal Astrocytic D2-otr Heteromersmentioning
confidence: 99%
“…The potential clinical usefulness of OT as adjunctive drug therapy in PD patients would be therefore based also on the possibility to reduce the dopaminergic therapy side effects, including the impulsivity disorders mainly in patients with addictive behaviors. As a matter of fact, evidence in animal PD models is provided that OT administration may possess neuroprotective effects on dopaminergic neurons related to anti-inflammatory, antioxidant, and anti-apoptotic activities [103], that dopamine levels increased when OT was administrated [104], that the OT levels were decreased in the models, that OT supplementation rescued locomotor disabilities and anxiety-like behaviors [101], and that after intranasal administration OT concentrates in brain regions including the striatum [105]; nevertheless, studies investigating OT in PD clinical settings are still needed [106]. In fact, critical examinations appear fundamental for enabling the utilization of OT mechanisms as a curative tool in psychiatric disorders, in particular when considering that the understanding of how OT impacts social behavior is still insufficient, life experience can change the OT systems function, and the OT effects appear highly context-dependent [107].…”
Section: Potential Relevance Of Striatal Astrocytic D2-otr Heteromersmentioning
confidence: 99%
“…Our findings demonstrated that there was no significant difference between the TAS/TOS levels and the OSI in the serum of the Ctrl and PTZ groups. OT may have antioxidant effects in different organs; however, we can conclude that OT may not act as an antioxidant in the serum of PTZ-kindling rats. We only calculated TAS and TOS levels and the OSI after the 3rd day of the last PTZ injections.…”
Section: Resultsmentioning
confidence: 69%
“…OXT signaling with OXTRs has been shown to inhibit activated microglia and increase the number of NKCs, a phenomenon documented in schizophrenia [221]. Recently, an OXT-generating microglial population was identified, suggesting that anti-inflammatory microglia may regulate many physiological functions that could cause pathology when disrupted [222,223].…”
Section: Oxtmentioning
confidence: 99%